2022
DOI: 10.1155/2022/1883293
|View full text |Cite
|
Sign up to set email alerts
|

Patient Family Binding and Authentication Scheme with Privacy Protection for E-Health System

Abstract: The emergence of the E-health system has brought convenience to many chronically ill patients and elderly people with limited mobility. With the help of the E-health system, patients can upload their physiological data timely and get a diagnosis at home, which is more convenient and efficient as they do not have to line up in hospitals. In order to ensure this convenience while protecting patients’ privacy, many schemes have been proposed which can help patient and medical server authenticate each other. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…, where e 2 is the length of R j and e 2 is also a big positive integer [36]. From this, it can be concluded that the probability of A guessing the correct response is negligible.…”
Section: Definition 1 (Ecddhp)mentioning
confidence: 85%
“…, where e 2 is the length of R j and e 2 is also a big positive integer [36]. From this, it can be concluded that the probability of A guessing the correct response is negligible.…”
Section: Definition 1 (Ecddhp)mentioning
confidence: 85%